2008
DOI: 10.1186/1742-2094-5-22
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis optica pathogenesis and aquaporin 4

Abstract: Neuromyelitis optica (NMO) is a severe, debilitating human disease that predominantly features immunopathology in the optic nerves and the spinal cord. An IgG1 autoantibody (NMO-IgG) that binds aquaporin 4 (AQP4) has been identified in the sera of a significant number of NMO patients, as well as in patients with two related neurologic conditions, bilateral optic neuritis (ON), and longitudinal extensive transverse myelitis (LETM), that are generally considered to lie within the NMO spectrum of diseases. NMO-Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
115
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 140 publications
0
115
0
6
Order By: Relevance
“…With regard to the role of AQP4 in brain inflammation, AQP4 expression is associated with inflammation in multiple sclerosis, human immunodeficiency virus encephalitis or progressive multifocal leukoencephalopa-thy [8] , experimental autoimmune encephalomyelitis [9,10] , neuromyelitis optica (NMO) [11,12] , hemorrhage [13] or after intracerebral injection of lipopolysaccharide [14] or lysolecithin [15] . Especially in NMO, an inflammatory autoimmune demyelinating disease, AQP4 is a specific target because an IgG1 autoantibody (NMO-IgG) against AQP4 has been identified in the sera of a significant number of NMO patients [11,12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the role of AQP4 in brain inflammation, AQP4 expression is associated with inflammation in multiple sclerosis, human immunodeficiency virus encephalitis or progressive multifocal leukoencephalopa-thy [8] , experimental autoimmune encephalomyelitis [9,10] , neuromyelitis optica (NMO) [11,12] , hemorrhage [13] or after intracerebral injection of lipopolysaccharide [14] or lysolecithin [15] . Especially in NMO, an inflammatory autoimmune demyelinating disease, AQP4 is a specific target because an IgG1 autoantibody (NMO-IgG) against AQP4 has been identified in the sera of a significant number of NMO patients [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Especially in NMO, an inflammatory autoimmune demyelinating disease, AQP4 is a specific target because an IgG1 autoantibody (NMO-IgG) against AQP4 has been identified in the sera of a significant number of NMO patients [11,12] . NMO-IgG down-regulates AQP4 in astrocytes, leads to the accumulation of toxic molecules and astrocyte dysfunction, and thereby results in demyelination and aggravates edema [12,16,17] .…”
Section: Introductionmentioning
confidence: 99%
“…An intrinsic link between SS and NMOSD has been suggested 12 . The human salivary glands possess aquaporin-3 and aquaporin-5 channels 13 ; AQP4 channels have been found in rodent salivary glands 14 .…”
Section: Rheumatologymentioning
confidence: 99%
“…The human salivary glands possess aquaporin-3 and aquaporin-5 channels 13 ; AQP4 channels have been found in rodent salivary glands 14 . Autoimmunity in the salivary gland, in the context of SS, may result in an immune response against AQP4 12 . Previous studies have suggested that patients with SS with neurologic deficits should have an examination for NMOSD 15 .…”
Section: Rheumatologymentioning
confidence: 99%
“…Aquaporin (AQP)-1 is natively expressed in the choroid plexus and contributes to water transport across the choroidal epithelium during CSF secretion. AQP-4 is more widely distributed within the CNS, including the choroid plexus [13] and ependymal cells of the ventricles [9]. Bloch et al [4] suggested that AQP-4 could facilitate CSF absorption in hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%